Goods Traffic and the Economy - Frank Bruns (Revue de Géographie Alpine)
Transport through and within the Alps is continuously increasing. In the Alpine transit corridors the negative effects of transport on humans and the environment are felt particularly. From the focus point of the affected Alpine regions, a sustainable development solution for this problem is required as soon as possible. Any suggestions in order to solve this problem should be discussed in view of all the facts: Thus, the relationship between “freight transport and the Economy/Society” also need to be taken into account. In this context, the central issue is that the impact of transport on the economy and society will differ depending on the economic potential and the reaction of players in the relevant region. Within the project MONITRAF the respective relationships has been investigated and indicators identified (BRUNS F., DELB V., 2005).